2019
DOI: 10.1242/bio.034215
|View full text |Cite
|
Sign up to set email alerts
|

Tpl2 is required for VEGF-A-stimulated signal transduction and endothelial cell function

Abstract: New blood vessel sprouting (angiogenesis) and vascular physiology are fundamental features of metazoan species but we do not fully understand how signal transduction pathways regulate diverse vascular responses. The vascular endothelial growth factor (VEGF) family bind membrane-bound receptor tyrosine kinases (VEGFRs), which trigger multiple signal transduction pathways and diverse cellular responses. We evaluated whether the MAP3K family member and proto-oncoprotein Tpl2 (MAP3K8) regulates basal and VEGF-A-st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 50 publications
1
5
0
Order By: Relevance
“…We have previously identified a signalling nexus between VEGFR2, the MAP3K family member Tpl2, and a transcription factor, ATF-2. In previous studies on VEGF-Astimulated and ATF-2-regulated endothelial gene expression on VCAM-1 [15] and Tpl2 [16], we find that maximal VEGF-A165-stimulated, ATF-2-regulated VCAM-1 synthesis occurs 8 h after VEGF-A addition. Under such conditions, there is complexity in decreased VEGFR2 levels caused by increased ubiquitination, endocytosis and degradation [15].…”
Section: Atf-2 Modulates P21 P53 and Cyclin D1 Levelssupporting
confidence: 45%
See 3 more Smart Citations
“…We have previously identified a signalling nexus between VEGFR2, the MAP3K family member Tpl2, and a transcription factor, ATF-2. In previous studies on VEGF-Astimulated and ATF-2-regulated endothelial gene expression on VCAM-1 [15] and Tpl2 [16], we find that maximal VEGF-A165-stimulated, ATF-2-regulated VCAM-1 synthesis occurs 8 h after VEGF-A addition. Under such conditions, there is complexity in decreased VEGFR2 levels caused by increased ubiquitination, endocytosis and degradation [15].…”
Section: Atf-2 Modulates P21 P53 and Cyclin D1 Levelssupporting
confidence: 45%
“…There is link between VEGF-A-stimulated ATF-2 phosphorylation and ATF-2 levels [15,16]. Activation of the p53 tumour suppressor is known to increase levels of p21, a negative cell cycle regulator, thus potentially impacting additional cell cycle modifiers including Cyclin D1 [18][19][20].…”
Section: Atf-2 Modulates P21 P53 and Cyclin D1 Levelsmentioning
confidence: 99%
See 2 more Smart Citations
“…TPL2 also plays a crucial role in growth factor and chemokine-induced tumor angiogenesis. Recently, it was shown that angiogenic factors such as VEGF, EGF and CXCL1 induce TPL2 activation, which in turn modulates endothelial-leukocyte interactions, monolayer permeability and new blood vessel formation through the regulation of Akt, endothelial NOS (eNOS) and ATF-2 60 , 61 . Moreover, TPL2 serves as a downstream effector of CXCL1, bFGF and EGF, where it activates the transcription factors C/EBPβ, NF-κB and AP-1 that induce VEGF expression, thereby promoting tumor angiogenesis 19 , 61 .…”
Section: Tpl2 and Tumorigenesismentioning
confidence: 99%